Karakteristik dan Potensi Bakteri Rhizosfer Penghasil Indole Acetic Acid yang Berasosiasi dengan Tanaman Kopi (Coffea spp.) - Ervinda Yuliatin; Mamluatul Faizah (Pro-Life, 2023)
Coffee (Coffea spp.) consumption increased faster than five years ago. However, coffee production availability declined due to the limited field, soil nutrient deficiency, and chemical fertilizer. The aimed research was to obtain a bacteria-producing IAA hormone isolate and to evaluate its density and diversity in improving soil quality and fertility for coffee growth. The rhizosphere soil samples were collected around the coffee plantation in UBF at Sumberwangi, Malang. The sample was isolated using serial dilution on 0.85% NaCl and spread on a Tryptic soy agar medium. The result revealed that the total number of bacteria-producing IAA was 36 isolates, and two isolates (TAS1.2 and TAS 2.6) had higher IAA hormone production at 60 ppm. The selected bacteria can be optimized for a candidate of bacteria-based fertilizer coffee production. Keywords: IAA, density, diversity index, PGPR